Trinidad and Tobago. Annual report 2007 - Instituto Interamericano de Cooperación para la Agricultura (IICA) (IICA, 2020)
The IICA Office in Trinidad and Tobago is guided by an annual work programme, which is set within and in response to the wider hemispheric and regional and national mandates of the Agro Plan 2003-2015, the Jagdeo Initiative and the Government of Trinidad and Tobago’s Vision 2020 respectively. The annual work programme is designed to respond to identified needs within the sector which the Office can reasonably and realistically attend to in its efforts to assist the country to achieve sustainable agricultural and rural development.